Alligatorweed flea beetle Agasicles hygrophila Selman and Vogt (Coleoptera: Chrysomelidae: Halticinae) - Ted D. Center; James P. Cuda; Michael J. Grodowitz (EDIS)
Alligatorweed is an aquatic weed native to South America that began threatening Florida’s waterways in the early 1900s. Alligatorweed flea beetles kill the plant by destroying its stored food and interfering with photosynthesis by removing leaf tissue. This insect has been an extremely effective biological control agent in coastal regions of the southeastern United States. This revised 3-page fact sheet was written by Ted D. Center, James P. Cuda, Michael J. Grodowitz, and published by the UF Department of Entomology and Nematology, October 2012.